1958
DOI: 10.1002/art.1780010404
|View full text |Cite
|
Sign up to set email alerts
|

Studies on dexamethasone, a new synthetic steroid, in rheumatoid arthritis—a preliminary report

Abstract: Observations concerning the antirheumatic and physiologic effects of a new synthetic corticosteroid, dexamethasone, are presented. This preparation, the most potent of any steroid heretofore studied, did not cause sodium retention or potassium loss in doses sufficient to suppress rheumatoid disease. Increased nitrogen and calcium excretion were observed. Further clinical studies are indicated. For the present, it is suggested that the daily dose of dexamethasone should not exceed 4 mg.Es presentate observation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
30
0
2

Year Published

1959
1959
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(33 citation statements)
references
References 11 publications
1
30
0
2
Order By: Relevance
“…Our balance studies (Nordin, 1961) have shown that the faecal calcium content in cases of steatorrhoea is slightly higher than that of normal subjects at the same intake levels, but the difference is a relatively small one. The results obtained in patients on steroid therapy are also compatible with our own previous observations and with those of other workers (Bunim et al, 1958;Slater et al, 1959). On moderate doses of corticosteroids the only consistent abnormality of calcium balance so far observed is an impairment of calcium absorption.…”
supporting
confidence: 93%
“…Our balance studies (Nordin, 1961) have shown that the faecal calcium content in cases of steatorrhoea is slightly higher than that of normal subjects at the same intake levels, but the difference is a relatively small one. The results obtained in patients on steroid therapy are also compatible with our own previous observations and with those of other workers (Bunim et al, 1958;Slater et al, 1959). On moderate doses of corticosteroids the only consistent abnormality of calcium balance so far observed is an impairment of calcium absorption.…”
supporting
confidence: 93%
“…The duration of suppression for triamcinolone was longer (about fifty-four hours), and was longest for dexamethasone and beta methasone (about sixty-six and seventy-six hours, respectively). Bunim et al (1958) reported that 1 mg of dexamethasone given at midnight resulted in total suppression of 8 a.m. plasma Cortisol, whereas 30 mg of prednisone was required for total suppression of plasma Cortisol the following morning. Since the anti-inflammatory activity of dexa methasone in rheumatoid arthritis was only il| six times tiiat of prednisone, it is apparent that equipotent doses of dexamethasone were much more suppressive of the HPAaxis than prednisone.…”
Section: Discussionmentioning
confidence: 97%
“…2 Au cours des deux décennies suivantes, l'utilisation de la dexaméthasone en tant qu'agent anti-inflammatoire puissant a été explorée, et on a rapidement découvert que le médicament offrait des avantages dans des situations cliniques telles que l'extraction des dents de sagesse 3 et la laryngotrachéobronchite aiguë (croup). 4 Il a fallu davantage de temps avant de reconnaître l'action antiémétique puissante de la dexaméthasone, bien que cet effet ait déjà été démontré dans les premières études.…”
Section: Innocuité Deunclassified
“…2 Over the following two decades, the use of dexamethasone as a potent anti-inflammatory agent was explored, and the drug was soon found to be beneficial in such clinical situations as third molar extraction 3 and acute laryngotracheobronchitis (croup). 4 The potent antiemetic action of dexamethasone was somewhat slower to be recognized, even though this had been shown in early studies.…”
mentioning
confidence: 99%